SISTEM INFORMASI BERBASIS WEB PUBLISITAS KELOMPOK WANITA TANI DAN DESA WISATA SITU LEBAK WANGI DI DESA PAMEGARSARI - Mohammad Reza Fahlevi (Universitas Negeri Medan, 2023)
Pamegarsari Village has several advantages, precisely in Lebak Wangi Village. These advantages include the tourist village of Situ Lebak Wangi and a group of organizations in the Tajur village called the Women's Farmers Group, known as KWT. In the world of agriculture, farmers expect suppliers to cooperate with farmers. The reason is that the profits obtained are greater than cooperation with middlemen. KWT Pamegarsari Village is a small farm that produces vegetable and herbal plant products. The lack of information media makes KWT and this tourist village not known to the outside community. A website-based information system is one source of information related to the advantages of Pamegarsari Village. With this website, it can make it easier for outsiders to find more information regarding the tourist village of Situ Lebak Wangi, make it easier for suppliers to collaborate with KWT farmers, and promote products from vegetable crops and herbal crops to outsiders. This is to increase the income of Pamegarsari Village and spark innovation to be used as an example by other villages.